Identifikasi Pembelajaran Jarak Jauh Melalui Internet Dalam Masa Pandemi COVID-19 di SMA Negeri 1 Dampal Utara Kabupaten Toli-Toli - Nilda; Novarita, Amalia (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2023)
The purpose of this research is to explain and identify the obstacles encountered in identifying online learning in geography during the COVID-19 pandemic at SMA Negeri 1 Dampal Utara, Toli-Toli Regency. This type of research is qualitative research with a descriptive approach. The subjects of this study were 2 geography teachers and students. The types of data to be used in this study used primary data and secondary data. The data analysis technique has three steps, namely: data reduction, data display, and conclusion. The results of this study are 1) Identification of online learning has been carried out quite well. Teachers and students use Whatsapp even though learning is done online the teacher continues to plan lessons by making lesson plans online. In addition WhatsApp is used to share information related to learning. 2) Identification of teacher learning using media in the form of video, aims to make it easier for students to understand the material. In addition, the method used by the teacher is adjusted to the characteristics of the students, the teacher uses the lecture method, the assignment method. 3) the obstacles faced by teachers regarding learning videos, because they have to match the material to be taught, and the teacher's constraints regarding insufficient cellphone memory. After providing the video, does the student see it or ignore it and that is also an obstacle for a teacher who cannot monitor his students.